Prediction of progression to muscle-invasive disease in patients with high-risk bladder cancer - Oszczudlowski, Maciej; Dobruch, Jakub (Translational Andrology and Urology; Vol 7, No 4 (August 15, 2018): Translational Andrology and Urology (Male Genitourinary Reconstruction and Trauma), 2018)
Despite complete transurethral resection of bladder tumor (TURBT) and adjuvant intravesical treatment, relevant proportion of patients with non-muscle invasive bladder cancer (NMIBC) experience disease recurrence or progression (1).